A magia do cinema na praça:apropriação do espaço e sociabilidade em Salvador-BA - Silva, Alzilene Ferreira da (2009)
It s in the city spaces, molded from the uses and daily appropriations, that life is woven, as a product of the social relationships from the accumulation of history along with the present day fabric. Within this relationship, the old and the new are elements which make up this tapestry, as a result of the contribution of successive generations. The public square is seen as an example of this relationship, since it consists of a fertile space for opportunities of urban life coexistence. It is within the trace of these considerations that the present study emerges regarding the appropriation and sociability of the Tomé de Sousa Square, located in the city of Salvador, BA, having as its main focus the special relation between the cinema and the public square, as it relates to the space of the exhibition of cinematographic art. The showing of films in public squares makes possible a distinctive means of appropriation which has occurred ever since the beginning of the cinema. Today in Brazil, projects of this nature abound, which aim at presenting the seventh art to a great portion of the population which doesn t have access to conventional movie theater projection rooms. This particular Projeto Cinema na Praça Cinema in the Square Project carried out in Salvador, has become the empirical reference point for such work. This journey reveals the fascination that this great art has woven through time, attracting and charming multitudes. The cinema touches people in a special way, stirring up affectionate feelings, which are reflected in multiple social practices. Regarding this work, what stands out above all are the projections in the squares, initiatives which make it possible for the films to be watched collectively. What was taken into account in order to carry out this work were the reports of those who came regularly to watch the cinema in the Square sessions, those involved with the cinema projects team, and the film makers. To do the work, besides a bibliographical revision, observations were made of participants in the Tomé de Sousa Square, taken from semi-structured interviews with people involved with the film projection projects and those who came regularly to the cinema in the Square sessions. Also investigations were made in newspapers, printed magazines and the internet, from document and iconographic sources. The photographic documentation proved to be an important contribution to the field work. The research therefore develops from the understanding that the social practices are what make possible the uses of and the appropriation of the spaces. Within this perspective the public square emerges as a privileged locus where possibilities flourish for multiple manifestations that social practices can generate